Diminished Prolinemia in Chronic Chagasic Patients: A New Clue for Disease Pathology? - Rocha, Sandra Patricia (2019)
Trypanosoma cruzi, the etiological agent of Chagas disease, is dependent on proline for a variety of processes, such as energy metabolism, host cell invasion, differentiation, and resistance to osmotic, metabolic, and oxidative stress. On this basis, we investigated a possible relationship between prolinemia and severity of T. cruzi infection in chronic patients, as reported here. The study population consisted of 112 subjects, separated into 83 chronically T. cruzi‐infected patients and 29 age‐matched healthy volunteers (control) of both sexes, recruited at the Chagas Disease Service from the Department of Cardiology, Hospital Provincial del Centenario de Rosario (Rosario, Argentina). Chagasic patients were separated into three groups: chronic asymptomatic, mild/moderate, and severe chronic chagasic cardiomyopathy (CCC) subjects. We observed a significant decrease of 11.7% in prolinemia in chagasic patients when compared to controls. Further analysis within the three groups of chagasic patients also revealed a statistically significant decrease of prolinemia in severe CCC patients compared to controls, showing a relative difference of 13.6% in proline concentrations. These data point to the possibility that collagen—which participates in the healing process of cardiac tissue—and proline metabolism in the myocardium could constitute new factors affecting the evolution of Chagas disease.